Sony / Mohamad Amirul Amir Shafie - Amir Shafie, Mohamad Amirul (2022)
This assignment is about identifying the problem with the product. The company that I have chosen is Sony company. From their variety of products, I have chosen the Sony Xperia 10 III to do my analysis. In this case study, I have done the SWOT analysis to identify the strength, weaknesses, opportunities, and threats of the Sony Xperia 10 III. The main problem I identified on this Sony Xperia 10 III is slow charging problem. From the problem, I can come up with the best solution which is add new system development by using Vooc fast charging system in charger for Sony Xperia 10 III.